INOVASI PELAYANAN ADMINISTRASI KEPENDUDUKAN BERBASIS APLIKASI SI POLGAN DI DESA KRANDEGAN, PURWOREJO (STUDI KASUS PEMBUATAN SURAT KETERANGAN KELAHIRAN) - Solekhah, Nur; Widowati, Nina; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2024)
The Si Polgan application (Information System and Online Services of Krandegan Village) is an innovation initiated by the Krandegan Village Government to meet the community's needs regarding administrative services, particularly in population management, as the population increases, including the issuance of Certificate of Recognition of Birth. This application- based innovation can be accessed via Android smartphones. This research aims to analyze the attributes of application-based service innovations in the successful implementation of birth certificate issuance, as well as the driving and inhibiting factors of the Si Polgan application innovation in Krandegan Village. The application is analyzed using M. Rogers's innovation attributes theory to examine the research phenomenon and the supporting and inhibiting factors of implementing the Si Polgan application-based birth certificate issuance innovation, using Suwarno's theory. The research results indicate that the application-based Certificate of Recognition of Birth service innovation of Si Polgan in Krandegan Village is not yet optimal because it has not met the criteria of relative advantage, compatibility, complexity, triability, and observability. Supporting factors for this innovation include the desire for self-improvement, availability of facilities and infrastructure, freedom of expression, wise leadership, and a supportive environmental condition. However, there are inhibiting factors, such as administrative constraints, insufficient socialization, lack of rewards or incentives, and a culture of risk aversion.